PENDAMPINGAN PROGRAM TAHFIDZ MENGUNAKAN METODE UMMI DI TK TELKOM KOTA PADANG - Dedek Saputra; Martin Kustati; Gusmirawati Gusmirawati (LPPM Universitas Bina Bangsa, 2023)
The aim of the Tahfidz program assistance is by using the Ummi method at Telkom Kindergarten to assist students in the process of memorizing the Al-Qur'an, the method is a very important dynamic aspect, with the method the memorization process will be maximized. Therefore, Al-Qur'an tahfidz teachers must have a method for memorizing the Al-Qur'an for students. So that students who are lazy and bored in memorizing the Al-Qur'an do not stop halfway. The Ummi method is a practical method of reading the Qur'an properly and correctly. The basis of the Ummi method is the direct method (direct method without much explanation), repeatiiton (repeated) and sincere affection (ummi foundation), the Ummi method is a method or direct practical method that does not require much explanation and is repeated in learning to read the Koran. Based on these problems, it is necessary to use the ummi method in implementing the tahfiz program at Telkom Kindergarten. The method used in this mentoring is PAR (Participator Action Research). The results of this mentoring are: (1) Increasing students' ability to memorize the Al-Qur'an. (2) Increase students' understanding in memorizing their memorization. (3) Increasing students' enthusiasm in repeating their memorization. This activity was carried out at Telkom Padang Kindergarten and was carried out in accordance with the targets set. This activity has an impact on students being able to memorize the Al-Qur'an. This activity was carried out in an effort to improve the quality of the memorization process using the tabarak method. All students who take part in tahfiz learning are expected to be able to repeat, add to and improve their ability to memorize the Al-Qur'an